"Portugal's Public Opinion in the Context of Austerity: The Curious Case of Healthcare" - Popic, T.; Schneider, S.; Asensio, M. (Norface Welfare State Futures Thematic Workshop, 2017)
This paper analyses Portuguese public opinion toward healthcare in the context of crisis. Portugal stands out as one of the European countries strongly hit by the financial crisis. The Portuguese crisis manifested itself through the growing government's debt, rising unemployment and financial instability and prompted government's response characterized by a series of austerity measures. We investigate to what extent the changes brought in the Portuguese healthcare by crisis and austerity have been reflected in public opinion and whether the public opinion trends in the context of crisis can be explained with the dualization theory, which distinguishes between labor market 'insiders' and 'outsiders'. Applying the dualization theory to the Portuguese case, we expect differences between healthcare attitudes of 'insiders' and 'outsiders' in the context of crisis since reforms introduced during the crisis have changed the structure of opportunities for healthcare access and coverage for these two labor market groups by reducing opportunities for the former and improving them for the latter. The results of the empirical findings confirm this expectation, showing that 'insiders' during/after the crisis were significantly more negative in their evaluations of the Portuguese healthcare sector than 'outsiders'. The results also show that these labor market groups were not fully homogenous in their evaluations demonstrating, for example, that those 'insiders' with the most stable employment status, and therefore with the most secure and extensive opportunities for healthcare coverage, were more negative than workers on part-time and temporary contracts and therefore, more insecure healthcare opportunities. Our findings contribute to the literature on feedback effect and stress that the crisis-induced welfare state reforms must be analyzed in a more fine-grained way that pays attention to different effects of these reforms across social groups.